Sobre o teorema do cilindro em H²xR - Gomes, Tiago de Almeida (2023)
Considering cylinder in space hyperbolic product of dimension 2 with the straight line. In this dissertation we prove that a surface of the type product of a regular curve with the straight line, which is connected and complete, must satisfy the deﬁnition of cylinder if, and only if, the extrinsic and intrinsic curvatures are null. The text and demonstrations presented here is based on the article [1] " The Cylinder Theorem in H2 × R ".